A world health organization core drug use indicator based prescription study in the dermatology outpatient department of a tertiary care teaching hospital of central South India - Jaiswal, Mahendra K.; Chakrawarty, Rajnesh K.; Sharma, Sanat K.; Sharma, Raj K.; Bharti, Rupendra K.; Agrawal, Ratna (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Irrational prescribing is a universal problem that may lead to inadequate response to medication therapy, poor patient compliance and increased adverse drug reactions ultimately leading to frequent hospital admissions. Hence this study was done to assess the drug utilization pattern using WHO core drug use indicators so that the recommendation can be made towards the rational prescribing. Methods: A sample of 3650 prescriptions was analysed prospectively to assess the drug utilization patterns in the dermatology OPD of a tertiary care teaching hospital of central south India. Results: The average number of drugs per prescription was 2.74 whereas 79.26% drugs were prescribed by generic names. Percentage of encounters with an antibiotic prescribed was 18.68%. Regarding use of injections, 3.26% prescriptions contains one or more injections. Percentage of drugs prescribed from essential drugs list was 78.37%. Average consultation time was lower (2.9 minutes) than recommended. Conclusions: The data from the present study indicates that prevalence of polypharmacy, inadequate consultation and dispensing time along with poor patient’s knowledge are the areas of medication therapy to be improved. Availability of essential drugs and key drugs in stock should be improved to achieve rational therapeutic goal. Further, continued medical education regarding the rational prescribing will definitely improve the standards of health care delivery.